The Influence of Nature on Well-Being During the COVID-19 Pandemic: Views From New England Island Residents - Nicole Kras; Jennifer Keenan (Island Studies Journal)
Researchers are beginning to explore the impact of the COVID-19 pandemic on island populations, but little is known about the experiences of the residents of Nantucket and Martha's Vineyard in the Northeast region of the United States. In this study, islanders (N=41) provide insight into how spending time in nature influenced their well-being, especially their mental well-being, during this unprecedented time. For the majority of participants, the influence of nature on their well-being increased during the pandemic. Additionally, participants shared benefits of island living such as isolation from the mainland, as well as challenges such as food and supply shortages. Results from this study indicate that further research is needed around the importance of nature on well-being, especially mental health, for island residents.